Prevalence of Plasmid-Mediated Determinants With Decreased Susceptibility to Azithromycin Among Shigella Isolates in Anhui, China - Liu, Yanyan; Li, Hongru; Lv, Na; Zhang, Yalong; Xu, Xihai; Ye, Ying; Gao, Yufeng; Li, Jiabin (Frontiers in Microbiology, 2020)
Objective The aims of this study were to describe azithromycin (AZM) susceptibility patterns among Shigella isolates in Anhui, China and identify predictors of resistance with mobile element-mediated genes. Methods A total of 517 non-duplicate Shigella isolates (449 S. flexneri and 68 S. sonnei) were collected in the Anhui Province of China from September 2011–September 2015, and screened for the plasmid-mediated genes of decreased susceptibility to AZM (DSA), using polymerase chain reaction amplification and sequencing. Conjugation experiments and pulsed-field gel electrophoresis were conducted for all mphA-positive DSA isolates. Results The DSA rate for 449 S. flexneri isolates was 33.6%, compared with 39.7% for 68 S. sonnei isolates. Among 161 DSA S. flexneri isolates, 93 (57.8%) carried the mphA gene. Among 27 DSA S. sonnei isolates, 11 (40.7%) carried the mphA gene. However, other plasmid-mediated DSA genes were not found in these isolates. A total of 89 transconjugants (95.7%) were obtained from 93 mphA-positive S. flexneri isolates through conjugation, and 10 transconjugants (90.9%) were obtained from 11 mphA-positive S. sonnei isolates. Furthermore, the minimum inhibitory concentrations (MICs) of AZM among 89 S. flexneri transconjugants ranged from 4 to 128 μg/mL, with an MIC50 of 8 μg/mL and MIC90 of 32 μg/mL. The MICs of AZM among 10 S. sonnei transconjugants ranged from 4 to 256 μg/mL, with an MIC50 of 8 μg/mL and MIC90 of 64 μg/mL. Thirteen clusters were found for mphA-positive S. flexneri, and five clusters were found for mphA-positive S. sonnei. Furthermore, 10 homologous isolates among 13 mphA-positive S. flexneri isolates with high-level DSA were from Sixian county and were multidrug-resistant strains. Of the 10 homologous S. flexneri isolates, eight were from children (≤5 years old), and two from the elderly (>60 years old). Conclusion Our study demonstrates that the DSA for Shigella isolates was severe, and the plasmid-mediated mphA gene was the most common macrolide resistance gene detected in Shigella isolates collected in Anhui, China. The mphA-positive S. flexneri isolates with high-level DSA facilitated clonal spread in children and the elderly. This finding is noteworthy and warrants further study.